Long-term evaluation of benefits, harms, and cost-effectiveness of the National Bowel Cancer Screening Program in Australia: a modelling study. (July 2017) - Lew, Jie-Bin; St John, D James B; Xu, Xiang-Ming; Greuter, Marjolein J E; Caruana, Michael; Cenin, Dayna R; He, Emily; Saville, Marion; Grogan, Paul; Coupé, Veerle M H; Canfell, Karen
Summary: Background: No assessment of the National Bowel Screening Program (NBCSP) in Australia, which considers all downstream benefits, costs, and harms, has been done. We aimed to use a comprehensive natural history model and the most recent information about cancer treatment costs to estimate long-term benefits, costs, and harms of the NBCSP (2 yearly immunochemical faecal occult blood testing screening at age 50–74 years) and evaluate the incremental effect of improved screening participation under different scenarios. Methods: In this modelling study, a microsimulation model, Policy1-Bowel, which simulates the development of colorectal cancer via both the conventional adenoma-carcinoma and serrated pathways was used to simulate the NBCSP in 2006–40, taking into account the gradual rollout of NBCSP in 2006–20. The base-case scenario assumed 40% screening participation (currently observed behaviour) and two alternative scenarios assuming 50% and 60% participation by 2020 were modelled. Aggregate year-by-year screening, diagnosis, treatment and surveillance-related costs, resource utilisation (number of screening tests and colonoscopies), and health outcomes (incident colorectal cancer cases and colorectal cancer deaths) were estimated, as was the cost-effectiveness of the NBCSP. Findings: With current levels of participation (40%), the NBCSP is expected to prevent 92 200 cancer cases and 59 000 deaths over the period 2015–40; an additional 24 300 and 37 300 cases and 16 800 and 24 800 deaths would be prevented if participation was increased to 50% and 60%, respectively. In 2020, an estimated 101 000 programme-related colonoscopies will be done, associated with about 270 adverse events; an additional 32 500 and 49 800 colonoscopies and 88 and 134 adverse events would occur if participation was increased to 50% and 60%, respectively. The overall number needed to screen (NNS) is 647–788 per death prevented, with 52–59 colonoscopies per death prevented. The programme is cost-effective due to the cancer treatment costs averted (cost-effectiveness ratio compared with no screening at current participation, AUS3014 [95% uncertainty interval 1807–5583] per life-year saved) in the cost-effectiveness analysis. In the budget impact analysis, reduced annual expenditure on colorectal cancer control is expected by 2030, with expenditure reduced by a cumulative AUS1·7 billion, AUS2·0 billion, and AUS2·1 billion (2015 prices) between 2030 and 2040, at participation rates of 40%, 50%, and 60%, respectively. Interpretation: The NBCSP has potential to save 83 800 lives over the period 2015–40 if coverage rates can be increased to 60%. By contrast, the associated harms, although an important consideration, are at a smaller magnitude at the population level. The programme is highly cost-effective and within a decade of full roll-out, there will be reduced annual health systems expenditure on colorectal cancer control due to the impact of screening. Funding: Australia Postgraduate Award PhD Scholarship, Translational Cancer Research Network Top-up scholarship (supported by Cancer Institute NSW) and Cancer Council NSW.